2009
DOI: 10.1007/s11999-009-0934-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved Tendon Radioprotection by Combined Cross-linking and Free Radical Scavenging

Abstract: Allograft safety is a great concern owing to the risk of disease transmission from nonsterile tissues. Radiation sterilization is not used routinely because of deleterious effects on the mechanical integrity and stability of allograft collagen. We previously reported several individual cross-linking or free radical scavenging treatments provided some radioprotective effects for tendons. We therefore asked whether a combination of treatments would provide an improved protective effect after radiation exposure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 43 publications
2
21
0
2
Order By: Relevance
“…Furthermore, the evaluated D 10 values coincide with the results of other studies, which investigated the virus inactivation by gamma irradiation. It confirms the findings from Seto et al [28,40] and Dziedzic-Goclawska et al [31] who proclaimed a comparable impact of Ebeam and gamma irradiation. HIV-2 was the most resistant virus in this study what seems to be contrary to the results of Pruss et al [20] where the investigated parvovirus was the most resistant virus.…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, the evaluated D 10 values coincide with the results of other studies, which investigated the virus inactivation by gamma irradiation. It confirms the findings from Seto et al [28,40] and Dziedzic-Goclawska et al [31] who proclaimed a comparable impact of Ebeam and gamma irradiation. HIV-2 was the most resistant virus in this study what seems to be contrary to the results of Pruss et al [20] where the investigated parvovirus was the most resistant virus.…”
Section: Resultssupporting
confidence: 87%
“…Methods to reduce the effect of irradiation or recover allograft strength therefore remain important to pursue. Irradiated bone allograft can be subjected to free radical scavenger treatment or crosslinking agents to restore some of the strength of the collagen backbone after testing [3,39,58,61,62]. Our study provides an S-N relationship at standard radiation dose, which can be useful in future studies that seek to maintain allograft strength after sterilization.…”
Section: Discussionmentioning
confidence: 96%
“…Seto et al (2008Seto et al ( , 2009 and Ng et al (2013) demonstrated improved tangent modulus and strength in tendons treated with exogenous collagen crosslinking prior to Îł-irradiation sterilization than in conventionally irradiated tendons. Perhaps due to reports suggesting that extra crosslinking in healthy bone leads to embrittlement (Currey et al, 1995;Vashishth et al, 2001;Willett et al, 2013), crosslinking before or during irradiation of bone has not been previously tested.…”
Section: Introductionmentioning
confidence: 95%